Analisis faktor-faktor determinan perilaku inovatif karyawan di organisasi - Sriwardani, Sriwardani; Fajar, Fitriani; Maria, Santi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In entrepreneurship, innovation has been seen as one of the crucial aspects that can determine performance. Innovative behavior is also one of the things considered to encourage innovation, especially for individuals who work in creative industry businesses. The purpose of this study was to examine and understand the effect of proactive personality, peer support, and creative self-efficacy on the innovative behavior of creative workers. Through a quantitative approach, this research was conducted on 90 MSME employees in two cities in West Java Province, namely Bandung and Cirebon. The sample in this study was selected using a purposive sampling technique, with criteria for MSME employees who have been running their business for at least 1 year. Researchers distributed questionnaires to respondents through an online platform. The collected data was then analyzed using multiple regression analysis with the help of SPSS 25 software for windows. The results of this study contribute to the following findings. First, proactive personality was found to have a positive influence on the innovative behavior of entrepreneurs. Second, peer support also has a positive effect on innovative behavior. Finally, this study proves that creative self-efficacy has a positive influence on the innovative behavior of MSME employees in West Java, Indonesia. This research also provides some contributions that can be considered by the literature and practice in business and entrepreneurship, especially in developing countries.